Relationship between species diversity, biomass and light transmittance in temperate semi‐natural grasslands: is productivity enhanced by complementary light capture?. (14th July 2015) - Feßel, Carola; Meier, Ina C.; Leuschner, Christoph
Abstract: Question: A positive plant diversity–above‐ground productivity relationship is often demonstrated in synthetic grassland stands established for functional biodiversity research, but this relationship is rarely found along diversity gradients in natural and semi‐natural grasslands. One of the key mechanisms proposed to cause a positive species diversity–above‐ground productivity relationship is increased complementarity in resource use. Using light transmittance to the ground as a measure of resource use intensity in semi‐natural grasslands, we tested the hypothesis that peak above‐ground biomass (as a proxy for productivity) increases and light transmittance decreases with increasing species richness, which would reflect higher complementarity in light capture. Location: Semi‐natural temperate grasslands in Lower Saxony, Germany. Methods: We investigated 31 grasslands with variable species richness on three different geological substrates (greywacke, limestone and sandstone) at two spatial scales (sub‐regional and regional). Results: Structural equation modelling (SEM) and generalized linear models (GLM) revealed that species richness (5–22 species · 0.09 m −2 ) was negatively related to above‐ground biomass (AGB; 200–1350 g·m −2 ) and sward cover. The most influential determinant of AGB at the regional scale was temperature. Light transmittance was determined by sward cover, the cover of competitive species and AGB at the regional, and in part also at the sub‐regional level. We found no evidence for increased light capture complementarity with higher species richness. Conclusion: This suggests that competitive exclusion, but not complementarity in above‐ground resource use, mediates above‐ground productivity in species‐rich plant assemblages. Abstract : One of the key mechanisms proposed to cause a positive species diversity – productivity relationship is greater resource use complementarity. We tested this hypothesis with respect to greater complementarity in light capture for semi‐natural temperate grasslands with variable species richness at two spatial scales. We found evidence that competitive exclusion, and not complementarity in above‐ground resource use, mediates above‐ground productivity in species‐rich assemblages.